Аквадар: сказки / Катя Матюшкина - Матюшкина Екатерина Александровна (АСТ, 2016)
Экземпляры: ДБ (20160729) / Инвентарный номер: 48329 / Цена: 252.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 35 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6